Model Problem Based Learning Berbantuan Artifisial Intelegence (AI): Strategi Pengembangan Berpikir Kritis Mahasiswa PAI UIN Mataram - Muhammad Taisir; Mauzifa Mauzifa (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
In the context of learning in Islamic higher education, critical thinking skills are an essential competency, especially in Contemporary Fiqh courses that require an understanding of current and contextual issues. However, students still face obstacles in developing these skills due to the dominance of conventional learning methods. The Problem-Based Learning (PBL) model integrated with AI is offered as an innovative approach to promote active, collaborative, and exploration-based learning. This study aims to analyze the application of the AI-integrated PBL model in teaching Contemporary Fiqh on the topic of “Pornography and Pornographic Actions from an Islamic Perspective” and to examine its impact on the critical and creative thinking abilities of fourth-semester students in the Islamic Education Study Program at UIN Mataram. The method used was a quasi experiment with data collection techniques through tests, questionnaires, interviews, observations, and documentation. Data analysis included testing the validity and reliability of the instruments, testing normality and homogeneity, and testing hypotheses with Mann Whitney to see the effect and Spearman Rank to determine the direction of the relationship between variables. The results showed that the application of the AI integration PBL model was able to improve the quality of Contemporary Fiqh learning. Students were more active, responsive, and adaptive during the learning process. The application of this model had a positive impact on improving students' critical thinking skills, as reflected in their ability to recognize problems, collect and organize information, distinguish between facts and opinions, and evaluate information objectively.